An Examination of Maternal Contributors and Potential Modifiers of Fetal Growth in Pregnancy - Ferraro, Zachary Michael (Université d'Ottawa / University of Ottawa, 2012)
A greater understanding of critical periods of body weight regulation, including pregnancy, may aid in efforts to optimize weight management strategies for the mother and her baby. The gestational period has been implicated to play, in the child, a vital role in the developmental origins of obesity and other cardiometabolic diseases later in life. Therefore, we initially examined existing literature on the role of maternal obesity and its link to pediatric obesity and documented the known underlying physiological mechanisms responsible for this relationship while suggesting potential intervention targets that may improve maternal-fetal outcomes. In a second paper, we aimed to quantify maternal predictors of large for gestational age (LGA) neonates in the Ottawa and Kingston (OaK) birth cohort with specific hypotheses verifying the independent contribution of maternal prepregnancy body mass index (BMI) and excessive gestational weight gain (GWG) to fetal overgrowth. This paper also highlights the clinical utility of the revised 2009 Institute of Medicine GWG guidelines and discusses the potential role of physiological factors underlying the observed associations between BMI, excessive GWG and LGA neonates. As a follow-up to our population-level analysis (i.e., OAK cohort), papers three and four highlight how the insulin-like growth factor (IGF) axis, a vital regulator of growth and development, may be compromised at the molecular level in cases of maternal obesity (paper 3) and excessive GWG (paper 4). In paper 3 we show that maternal obesity is associated with attenuated expression of IGF binding protein-4 (IGFBP4) in umbilical cord blood and discuss how this may preferentially promote fetal adipogenesis. The effects of excessive GWG on IGF axis protein expression are addressed in paper four where we show that excessive weight gain during pregnancy is associated with increased expression of IGFBP3 in maternal circulation in normoglycemic term pregnancies. In this paper we discuss the potential inhibitory role of IGFBP3 on adipogenesis and how it relates to glucose intolerance during pregnancy. Recognizing that both obesity and excessive GWG can alter physiological processes in mother and her baby, appropriate evidence-based interventions are warranted to best optimize outcomes. In paper five, we discuss the results of a study which sought to assess patient information channels and knowledge of nutrition and physical activity during pregnancy with the intent that these findings be applied to best design efficacious strategies that cater to the needs of our target group of pregnant women. In our analysis we show that the majority of pregnant women studied would be willing to participate in a lifestyle intervention for their own personal health and that of their child. Of great interest was the observation that most women were not informed of the importance of pregnancy-specific energy intake, or made aware of their own healthy GWG targets. Additionally, many of the respondents reported receiving no information pertaining to appropriate physical activity recommendations; despite the fact that the vast majority of participants consider this lifestyle modality to be safe during their pregnancy. Finally in paper six, we build on the results of our previous work and evaluate the risks and benefits of physical activity during pregnancy on maternal-fetal outcomes through a review of the literature and note that engaging in non-sedentary pursuits during gestation may aid in maternal weight regulation, protect against metabolic disorders and optimize neonatal birth weight and body composition. Overall, the collective nature of the papers presented in this dissertation provides qualitative and quantitative evidence to support not only the complexity of body weight regulation in the mother and her baby, but also highlights potential avenues for intervention that may improve maternal-fetal outcomes during this critical period.
Keywords: Maternal obesity; Gestational weight gain; fetal; macrosomia; insulin-like growth factor; physical activity; exercise; developmental origins of disease; metabolism; insulin resistance; adiposity; pregnancy; lifestyle intervention; pediatric obesity; large for gestational age; fetal programming; insulin-like growth factor binding protein; nutrition; developmental programming; plasticity